Targeted Therapeutic Strategies in the Battle Against Pathogenic Bacteria - Yang, Bingqing; Fang, Dan; Lv, Qingyan; Wang, Zhiqiang; Liu, Yuan (Frontiers in Pharmacology, 2021)
The emergence and rapid spread of antibiotic resistance in pathogenic bacteria constitute a global threat for public health. Despite ongoing efforts to confront this crisis, the pace of finding new potent antimicrobials is far slower than the evolution of drug resistance. The abuse of broad-spectrum antibiotics not only accelerates the formation of resistance, but also imposes a burden on the intestinal flora, which acts a critical role in human homeostasis. As such, innovative therapeutic strategies with precision are pressingly warranted and highly anticipated. Recently, target therapies have achieved some breakthroughs by the aid of modern technology. In this Review, we provide an insightful illustration of current and future medical targeted strategies, including narrow-spectrum agents, engineered probiotics, nanotechnology, phage therapy and CRISPR-Cas9 technology. We discuss the recent advances and potential hinders of these strategies. Meanwhile, the possibility to mitigate the spread of resistance in these approaches are also mentioned. Altogether, a better understanding of the advantages, disadvantages and mechanisms of action of these targeted therapies will be conductive to broadening our horizons and optimizing the existing antibacterial approaches.